Relational aspects of decisions to sell - Jefferson, Therese; Taplin, Ross (Elsevier Inc., 2012)
Mental accounting has been identified as an important source of non-fungibility in household and individual decision making. Ostensibly uniform assets, including cash, are perceived differently according to their originating source. In this study we examine assumptions of fungibility by using scenarios within a factorial survey to compare the effects of four specific factors on individuals’ willingness to trade a specified possession that varies according to its relational source, dollar value, uniqueness and the potential buyer's identity. Two measures of willingness to trade are used; a composite distress measure and the minimum price that the participant is willing to accept in exchange for the possession. In addition, data are analyzed to explore relationships between willingness to sell, the four defined characteristics of the possession and participant's characteristics including age, gender, education and income. The possession's source and the buyer's identity dominate effects over the possession's value and uniqueness. The strength of the effects varies significantly depending on how distress is measured and between identifiable population groups.